Analisis Penerapan Protokol Kesehatan oleh Maskapai Citilink di Bandar Udara Internasional Minang Kabau Padang - Amanda novrianti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Implementation oh health protocol at citilink airlines, all officers who work in airport area or all prospective to comply with the health or SOP protocols of the pandemic. Applying health protocols is expected to minimize the spread of the covid-19 virus and create a world of aviation. This research is a qualitative kind. The method for collecting data in this study is interviews, observation, documentation, and library studies. The purpose of the study is to know how the application of health protocols to citilink airlines, and how the application of health protocols to the word of aviation will affect aircraft. Studies show that the application of health protocols in citilink airlines corresponds with the same SOP as it does. Based on the findings of the researchers, prospective passengers object to, regulations that require every prospective passenger to perform PCR.